Higher Education Quality Auditor Training in Vietnam - Nguyen Hoang Tien, Rewel Jiminez Santural Jose, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article studies the issues related to training, qualifying and certification of higher education quality auditors in Vietnam. Following the generic two-tier model of training and development of auditors, however Vietnam's methods of implementation are very different from the rest of the world and the ways of conducting are also very different in different regions of the country. The article analyzes and compares policies, experience, content and implementation of the auditor training programs in Vietnam compared with those of other countries in the world, thereby drawing suggestions for improvement solutions for autonomous auditing and accrediting agencies based auditors training centers and recommending policy changes to Vietnam's Ministry of Education and Training and related agencies such as the National Council for Higher Education Accreditation.